Effectiveness of a group intervention to reduce the psychological distress of healthcare staff: a pre-post quasi-experimental evaluation - Jeremy Dawson; Imelda McCarthy; Cath Taylor; Kristin Hildenbrand; Mary Leamy; Ellie Reynolds; Jill Maben (BMC, 2021)
Abstract Background Work stress and compassion fatigue are prevalent among healthcare staff and their negative effects on staff well-being and patient care are well-known. This paper reports on the implementation and evaluation of Schwartz Rounds® (Rounds) in UK healthcare organizations, predominantly part of the National Health Service (NHS). Rounds are one-hour, typically monthly, multidisciplinary forums during which clinical and nonclinical healthcare staff discuss the emotional and social demands of delivering patient care. The purpose of this research was to evaluate the effectiveness of Rounds attendance on the psychological distress, work engagement, compassion and self-reflection of healthcare staff. Methods We used a pre-post control design to assess the effect of Rounds attendance across 10 UK healthcare organizations. This design was most appropriate given the voluntary nature of Rounds and ensured the study had ecological validity. Self-reported data were collected from attenders and non-attenders at baseline and at eight-months follow-up. The outcomes were psychological distress, work engagement, compassion and self-reflection. Results During the 8 months' study duration, regular attenders (N = 51) attended Rounds on average 4 times (2-8). Attenders showed a significantly greater decrease in psychological distress (as measured with the General Health Questionnaire (GHQ)) than non-attenders (N = 233; odds ratio of 0.197; 95% confidence interval (0.047-0.823)). However, Rounds attendance had no significant effect on work engagement, compassion and self-reflection. Conclusions Rounds attendance was linked to a 19% reduction in psychological distress adjusting for covariates. As an organization-wide intervention, Rounds thus constitute an effective, relatively low-cost intervention to assist staff in dealing with the demands of their work and to improve their well-being.